A calcitonin secreting pancreatic neuroendocrine tumor with liver metastasis and hepatic vein thrombosis: a case report - Nina Piłka; Mateusz Drabczyk (Nicolaus Copernicus University in Toruń, 2024)
Pancreatic neuroendocrine neoplasms (PanNEN), accounting for only 1-2% of all pancreatic tumors, are slow-growing and capable of secreting substances that can cause characteristic clinical syndromes, with an increasing prevalence estimated at around 8-10 million cases per year. We report  the case of  a pancreatic neuroendocrine tumor with high calcitonin levels and distant metastases without clinical manifestation. The correct diagnosis of a neuroendocrine tumor was established based on histopathologic examination and immunohistochemical  assessment of the expression of neuroendocrine markers. The presence of somatostatin receptors led to the initiation of treatment with somatostatin analogues and radionuclide therapy. No increase in neuroendocrine tumor markers was observed. However, follow-up abdominal CT imaging performed after the completion of radionuclide therapy showed an unsatisfactory response with an increase  of liver metastases and an increase in the size of the primary tumor in the pancreas. Our case report contributes to the literature on the diagnostic challenges of neuroendocrine tumors and highlights the current debate regarding tumor mass cytoreduction.